Keefektifan Pembelajaran Kooperatif Tipe TGT dan GI Ditinjau dari Ketercapaian Standar Kompetensi, Sikap, Minat Matematika - Abd. Haris; Agus Maman Abadi (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2013)
Penelitian ini bertujuan untuk mendeskripsikan (1) keefektifan model pembelajaran kooperatif tipe TGT dan GI dan (2) mendeskripsikan perbandingan keefektifan model pembelajaran kooperatif tipe TGT dan GI ditinjau dari ketercapaian standar kompetensi, sikap, dan minat siswa terhadap matematika. Populasi penelitian ini adalah siswa kelas VII SMP Negeri 1 Unter Iwes Sumbawa yang terdiri atas 6 kelas. Dua kelas diambil secara acak sebagai sampel, yaitu kelas VII.3 dan VII.4. Kelas VII.3 belajar dengan model pembelajaran kooperatif tipe TGT, sedangkan kelas VII.4 belajar dengan model pembelajaran kooperatif tipe GI. Data penelitian dianalisis dengan uji One sample t test, uji T2 hoteling’s pada signifikansi 5% dan uji Independent t test. Hasil penelitian menunjukkan bahwa (1) pembelajaran matematika dengan model pembelajaran kooperatif tipe TGT dan GI efektif ditinjau dari ketercapaian standar kompetensi, sikap, dan minat siswa terhadap matematik dan (2) model pembelajaran kooperatif tipe TGT lebih efektif dibandingkan dengan model pembelajaran kooperatif tipe GI ditinjau dari ketercapaian standar kompetensi, sikap, dan minat siswa terhadap matematika.Kata Kunci: pembelajaran kooperatif, TGT, GI, ketercapaian standar kompetensi, sikap, minat. The Effectiveness of Cooperative Learning of TGT and GI Types in Terms of Achievement of Competence Standard, Attitude, Interest Mathematics AbstractThis study aims to describe (1) the effectiveness of cooperative learning model of TGT and GI type and (2) describe the comparison between the effectiveness of cooperative learning model of TGT and GI type in terms of achievement of competence standard, attitude, and interest of student toward mathematics. The research population was a Class VII student of SMP Negeri 1 Unter Iwes Sumbawa which consisted of 6 classes. Two classes, namely Class VII.4 and Class VII.3 as the research sample. Class VII.3 learned through the cooperative learning of TGT type and Class VII.4 learned through the cooperative learning of GI type. The data were analyzed using One sample t test, T2 Hoteling’s at the significance level of 5% and Independent t test. The results of the study show that: (1) mathematics learning with cooperative learning model of TGT and GI type is effective in terms of achievement of competence standard, attitude, and interests of student towards mathematic, and (2) cooperative learning model of TGT type is more effective compared with the cooperative learning model of GI type in terms of achievement of competence standard, attitude, and interest of student toward mathematics.Keywords: cooperative learning, TGT, GI, achievement of competency standard, attitude, interest.